Penguatan Kompetensi Digital Guru PKBM Maleo melalui Pelatihan Pemanfaatan Aplikasi Artificial Intelligence untuk Persiapan Pembelajaran - Aryani, Diah; Asri, Jefry Sunupurwa; Asianto, Andriyanti; Akbar, Habibullah; Sutejo, Bayu Sulistiyanto Ipung; Suharti, Dwi Sloria (Abdimas Universal, 2026)
The development of Artificial Intelligence (AI) technology has opened up new opportunities to improve the efficiency of the learning process, particularly in terms of how teachers can prepare teaching materials more innovatively and efficiently. However, the use of AI technology in education still faces several challenges, primarily due to teachers' limited digital literacy. The purpose of this Community Service (PKM) activity is to help PKBM Maleo teachers improve their digital competency by teaching them how to use AI applications, specifically ChatGPT, when preparing lessons. In this activity, Participatory Action Research (PAR) is the approach method used in this activity. PAR supports active partner participation in every step of the process, such as problem identification, program planning, training implementation, evaluation, and reflection. The training activity was held in January 2026 with 14 teachers participating, with the results of the activity evaluation carried out using pre-test and post-test methods to measure the level of participants' understanding of the material provided. The pre-test results showed a significant increase in participant understanding, with an average score of 97.14, while the post-test results showed an increase to 85.7% to 100%. The results of this PKM activity demonstrate that AI training with ChatGPT can help teachers improve their digital literacy skills and better prepare learning materials. It is hoped that this activity will encourage the wise and productive use of artificial intelligence technology in learning in non-formal schools.